Synthesis of bis(aryloxy)fluoromethanes using a heterodihalocarbene strategy - Recsei, Carl; Barda, Yaniv (Beilstein Journal of Organic Chemistry, 2021)
A side-product present in the herbicide pyroxasulfone was synthesized. The construction of a bis(aryloxy)fluoromethane moiety was necessary, for which no existing method was available. We report a simple, new procedure which we applied to the synthesis of some of these unusual structures.
Keywords: acetal; aryloxyfluoromethane; dihalocarbene; herbicide; organofluorine

(untitled) - Reichel, M.; Karaghiosoff, K. (Angew. Chem., Int. Ed., 2020)

(untitled) - Ni, F.; Li, J. (Synthesis, 2012)

(untitled) - Sperry, J. B.; Sutherland, K. (Org. Process Res. Dev., 2011)

(untitled) - Łaniewski, K.; Vågerö, M.; Forsberg, E.; Forngren, T.; Hagman, G. (J. Chromatogr. A, 2004)

WO Pat. Appl. - Bellina, R. F.; Bereznak, J. F.; Christensen, J. R.; Chang, Z.-Y.; Fawzi, M. M.; Marshall, E. A.; Moberg, W. K.; Rorer, M. P.; Sternberg, C. G.; Walker, M. P.; Zimmerman, W. T. (Fungicidal quinazolinones, 1998)

(untitled) - Platonov, V. E.; Malyuta, N. G.; Yakobson, G. G. (Russ. Chem. Bull., 1972)

(untitled) - Scheeren, J. W.; Staps, R. J. F. M.; Nivard, R. J. F. (Recl. Trav. Chim. Pays-Bas, 1973)

(untitled) - Scheibler, H.; Depner, M. (J. Prakt. Chem., 1958)

(untitled) - Wadzinski, T. J.; Steinauer, A.; Hie, L.; Pelletier, G.; Schepartz, A.; Miller, S. J. (Nat. Chem., 2018)

(untitled) - Cambanis, A.; Bäuml, E.; Mayr, H. (Synthesis, 1988)

(untitled) - Verhoog, S.; Pfeifer, L.; Khotavivattana, T.; Calderwood, S.; Collier, T. L.; Wheelhouse, K.; Tredwell, M.; Gouverneur, V. (Synlett, 2016)

WO Patent - Gandelman, M.; Nisnevich, G. A.; Kulbitski, K.; Artaryan, A. (Process for the preparation of organic bromides, 2017)

(untitled) - Jones, M. (Synthesis, 1984)

Encyclopedia of Reagents for Organic Synthesis - Matteson, D. S. (Dibromomethane, 2001)